PERUBAHAN RITUAL PERALIHAN TAHAP KELAHIRAN BUDAYA JAWA PADA MASYARAKAT DESA PURWOSARI I KECAMATAN TAMBAN KABUPATEN BARITO KUALA - Suhartiningsih Suhartiningsih (Universitas Lambung Mangkurat, 2014)
The Villagers of Purwosari I Tamban of Barito Kuala Regency are Javanese farmers who came from Java island (Blitar, Tulungagung, and Trenggalek), and they are very familiar with the ritual of the transitional phase even if they are not on their own land. Along with the changes of people’s live, the current transitional stage birth rituals also experiences changes from his predecessors. The purposes of this study were to describe: (1) a transitional stage of the ritual process of changing birth of Javanese people in Purwosari I village, (2) the factors that led to the shift or changes in transitional stages of birth ritual in Javanese culture in Purwosari I village. This research used the qualitative approach and techniques of data collection were interviews, observation and documentation. Purposive technique and snowball sampling determined the informants. The research results revealed that: (1) the ritual of birth transitional stage of Javanese culture for most Purwosari I villagers were still implemented as a complete and intact one, but there have been some shifts or changes, (2) The causes of the shifts in the ritual of birth transitional stage came from internal and external factors. The conclusions of this study are: (l) transitional stages of birth ritual of Javanese culture in some communities, especially in Purwosari I village has changed (2) the factors which caused changes to the ritual are classified as internal and external factors. Key words: ritual, transitional phase, and Javanese culture